Psycho-Social Factors And Resistance To Change In Post Merger Environment - Thamotharan, Parimala Devi (2002)
This study examines the resistance behaviour of the acquired by a financial organization following a merger with respect to selected psycho-social factors. The psycho-social factors that were included were Levenson's ( 1972) three orientations of locus of control i.e. internal, chance and powerful others, Jackson's (1959) R space model for person group relationships and an organizational variables, workers; perception of trust towards management.